2015
DOI: 10.1002/cbdv.201400305
|View full text |Cite
|
Sign up to set email alerts
|

Cumin (Cuminum cyminum L.) from Traditional Uses to Potential Biomedical Applications

Abstract: Cumin (Cuminum cyminum L.) is a small annual and herbaceous plant belonging to the Apiaceae family. It is a multipurpose plant species cultivated in the Middle East, India, China, and several Mediterranean countries, including Tunisia. Its fruit, known as cumin seed, is most widely used for culinary and medicinal purposes. It is generally used as a food additive, popular spice, and flavoring agent in many cuisines. Cumin has also been widely used in traditional medicine to treat a variety of diseases, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 46 publications
0
65
0
Order By: Relevance
“…A flavonoid quercetin (quercetin-3-O-α-L-rhamnopyranoside) obtained from Toona sinensis contained antioxidant with anticancer activities [ 84 ], whereas quercetin (quercetin 3-β-D-glucoside), isolated from Satureja montana was reported to be an antioxidant [ 85 ]. Despite of flavonoid, cumin shoots own metabolites having various pharmacological activities, such as antimicrobial, anti-daibetic, antiepileptic anti-infertility, anticancer, antioxidant and immunomodulatory [ 2 , 4 5 ]. Metabolites with bioactivity such as anticancerous (docetaxel) and antimicrobial (megalomicin) were also identified along with intermediate metabolites involved in different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A flavonoid quercetin (quercetin-3-O-α-L-rhamnopyranoside) obtained from Toona sinensis contained antioxidant with anticancer activities [ 84 ], whereas quercetin (quercetin 3-β-D-glucoside), isolated from Satureja montana was reported to be an antioxidant [ 85 ]. Despite of flavonoid, cumin shoots own metabolites having various pharmacological activities, such as antimicrobial, anti-daibetic, antiepileptic anti-infertility, anticancer, antioxidant and immunomodulatory [ 2 , 4 5 ]. Metabolites with bioactivity such as anticancerous (docetaxel) and antimicrobial (megalomicin) were also identified along with intermediate metabolites involved in different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It enhances the appetite, taste perception, digestion, vision, strength and lactation. It is also used in the treatment of fever, loss of appetite, diarrhea, vomiting, abdominal distension, edema and puerperal disorders [ 2 4 ]. Thus cumin seeds are of considerable importance because of its nutritional values and other health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Documented data revealed that Iranian medicinal plants and spices have strong antimicrobial effects, especially on variety of foodborne pathogens (Hajlaoui et al, 2010;Iacobellis, Lo Cantore, Capasso, & Senatore, 2005;Johri, 2011;Mnif & Aifa, 2015).…”
mentioning
confidence: 99%
“…It is native to the Mediterranean region and has long been used in traditional medicine as an antioxidant, antimicrobial, antispasmodic, antiseptic, stomachic, stimulant, astringent, diuretic, carminative, and emmenagogic agent (Hajlaoui et al, 2010;Iacobellis et al, 2005;Johri, 2011;Mnif & Aifa, 2015). However, it is mainly used as an antimicrobial agent with high antioxidant activities and especially as a preservative agent in foods (Hajlaoui et al, 2010;Iacobellis et al, 2005;Johri, 2011;Mnif & Aifa, 2015). It can also prevent food spoilage and putrefaction (Hajlaoui et al, 2010;Iacobellis et al, 2005;Johri, 2011;Mnif & Aifa, 2015;Pajohi et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation